On the interpretation of long-distance agreement in Border Lakes Ojibwe - Hammerly, Christopher; Mathieu, Éric (Natural language and linguistic theory, 2025)
The aim of this article is to show that long-distance agreement (LDA) in Border Lakes Ojibwe (Central Algonquian) correlates not with topicality, as claimed in past literature, but with evidentiality (direct evidence), a finding that adds to the set of existing evidential extensions of non-evidential categories (e.g., the perfect in Georgian, participles in Lithuanian, the conditional in French) and bolsters the view that verbal agreement can also correlate with special semantics. Another important observation introduced in this article is that LDA in Ojibwe typically occurs in contexts involving verbs of perception and cognition known as transitive animate . Based on these observations, we propose that these verbs are associated with a set of ϕ -features on matrix v , while selecting an evidential feature. The latter is associated with an extended projection principle (EPP) property, which allows the embedded external or internal argument to raise to the specifier of embedded C. Finally, we show that LDA in Border Lakes Ojibwe has epistemic extensions, which have to do with the speaker’s probability and commitment towards information expressed. In this connection, we also propose that the evidential effect exhibited by LDA in Border Lakes Ojibwe is of the epistemic, rather than the illocutionary type.